POTRET MURUNG ANJING KAMPUNG SEBAGAI SUMBER INSPIRASI PENCIPTAAN KARYA SENI LUKIS - Pratomo, Tatto Jiwo; Gozali, Amir (Sanggitarupa, 2021)
This Final Project report entitled Portrait of Murung Kampung Dog as a Source of Inspiration for the Creation of Paintings was created based on experiences and observations related to cases that befell the lives of mongrels, from neglect, neglect, abuse, to consumption by humans. From this source of inspiration, the author creates a painting that is expected to be an awareness, that in treating mongrels like human friends. Cultivation of this final project using the L.H Chapman method with three stages, namely efforts to find ideas, develop ideas and visualize. The process of realizing the work of applying the plaque technique using acrylic paint on canvas media. This Final Project shows the visual of mutt dogs that have experienced various sufferings and cruelties from humans. This final project presents 10 works of painting. Keywords: Moody Portrait, Country Dog, Painting